Pengembangan E-LKPD Berbasis PBL Menggunakan Flip PDF Professional untuk Meningkatkan Literasi Sains pada Materi Medan Magnet - Annisa Nur Fadhila (Lembaga Sosial Rumah Indonesia, 2022)
Nowadays literacy scientific is a demand that must be owned by everyone, both in everyday life and in the world of work. Physics functions as science communication with physics learning that cannot be separated from mastering basic physics concepts, theories or new problems that require answers through understanding. In a learning process, teaching materials are needed as a tool in the learning process, making it easier for students to understand the subject matter. The purpose of this study was to develop an E-LKPD based on the PBL model to improve scientific literacy on appropriate magnetic field materials based on the results of validity and effectiveness tests. This research uses development model ADDIE. The research data obtained from the development of the e-LKPD include the results of the average validation value of 82.61%, the results of the effectiveness test getting an N-gain of 0.39 so that the e-LKPD is categorized as being able to improve scientific literacy skills in the medium category.